Os nomes dos guerreiros menores da Ilíada: um estudo da antroponímia grega - Tatiana Alvarenga Chanoca (2022)
This thesis presumes that the use of the proper names in Homero is purposeful, and their meaning is associated to its bearer or to the context in which the character is introduced. Hence, this work aims to analyses the possible meanings of the minor warrior’s names in the Iliad – i.e., warriors whose relevance in the poem is minimal and about whom limited information is provided (occasionally none beyond the name itself) –, in order to show that their inclusion in the poem was not indiscriminate.